FUSULINIDS FROM ISOLATED QARARI LIMESTONE OUTCROPS (PERMIAN), OCCURRING AMONG JURASSIC-CRETACEOUS BATAIN GROUP (BATAIN PLAIN, EASTERN OMAN) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2013)
The Batain Group of the northeastern coastal plain of Oman consists of offshore and deeper water deposits that accumulated in the Batain Basin and which were subsequently obducted onto the eastern margin of Oman. The oldest deposits of the Batain Group are the marly limestones of the Qarari Unit that have been dated as Early to Late Permian or Murgabian by different workers. Recently discovered outcrops of the Qarari Unit from the northern Batain plain are richly fossiliferous including the occurrence of fusulinids in three separate outcrops. The fusulinids represented are two species of Skinnerella - a subgenus of Parafusulina: Parafusulina (Skinnerella) visseri Reichel and the new taxon P. (S.) arabica. The most likely age of the described fusulinids is estimated as Kubergandian. The major marine transgression of the Tethyan realm that began in the Yakhtashian-Bolorian appears to have begun earlier in the Batain Basin than in other parts of Arabia and the Gulf, where it is represented by the Khuff Formation of Murgabian-Dorashamian age.
Keywords: Permian; Fusulinids; Stratigraphy; Oman